DIBL and subthreshold swing effect on carbon nanotube field effect transistor - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz (2015)
Silicon based devices are getting problem with the limitation of channel length for fabrication of the miniature size. Short channel effects are creating such problem of the silicon devices. Thus CNT is a smart choice for replacement with the silicon. A brief analysis of the effect of short channel carbon nanotube field effect transistor (CNTFET) is elucidated in this paper. The analysis of the CNTFET model shows the Drain Induced Barrier lowering (DIBL) and sub-threshold Swing (S) of CNTFET with the channel of 14nm. The analysis of SS and DIBL shows the best electronics performance of CNT. High-k transistor can be fit for this material such as Hfo2 performs low subthreshold swing because of get large gate capacitance. This analysis is necessary for the design of a lower scaling channel of CNTFET.